2016
DOI: 10.1016/j.ijsu.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection for metastases from colorectal cancer in very elderly patients: New surgical horizons

Abstract: Liver resection for CRLM in carefully selected patients above the age of 75 can be performed with acceptable morbidity and mortality rates, similar to those in younger patients. Moreover, the severity of CRLM in elderly patients is proven to be lesser than in younger patients. Thus, we can conclude that advanced chronological age cannot be considered a contraindication to hepatic resection for CRLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 52 publications
6
29
0
Order By: Relevance
“…One additional study was included by checking cross references, taking the total number of included studies to 11 [27]. A total number of 4 studies were included comparing patients aged <75 years with patients aged >75 years [12, 28-30]. The characteristics of each study are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One additional study was included by checking cross references, taking the total number of included studies to 11 [27]. A total number of 4 studies were included comparing patients aged <75 years with patients aged >75 years [12, 28-30]. The characteristics of each study are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The weighted mean age of patients aged <75 years was 61.5 ± 6.7 years, whereas the weighted mean age of patients aged >75 years was 77.6 ± 1.6 years. Only 2 studies reported on comorbidity [28, 30], which showed that ­patients aged >75 years were affected more often by cardiovascular comorbidity (33 vs. 20%; p  = 0.03). There was no difference in respiratory comorbidity (7 vs. 4%; p  = 0.58) and diabetes mellitus (15 vs. 9%; p  = 0.19) compared with patients aged <75 years (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations